Gender-Specific Association Between Nighttime Sleep Duration and Falls Among Community-Dwelling Middle-Aged and Older Adults in China. (December 2022) - Zhang, Nan; Wang, Cui; Li, Yuli; Yang, Mei; Yang, Jing; Chen, Fenghui; Yan, Ping
This study was conducted using the data from 2015 China Health and Retirement Longitudinal Study (CHARLS). Gender-specific association between nighttime sleep duration (NSD) and falls were evaluated through multiple logistic regression by adjusting for confounding variables. Of the 22, 899 respondents, 18, 446 were eligible and 3, 144 (16.99%) had more than a single fall. Short and long NSD were associated with high occurrences of falls in the total and female population, but only a short NSD was associated with a high occurrence of falls in the male population. In conclusion, NSD was strongly and significantly associated with falls, but the association was gender-specific. Accordingly, increasing targeted, evidence-based and gender-specific preventions for NSD and sleep disturbance are necessary among primary care interventions to prevent falls.